I'm your emotional support animal : navigating our all woke, no joke culture - Carolla, Adam (Post Hill Press, 2020)
Challenges today's social-media-driven society and its legitimizing of mainstream anxiety, lampooning subjects ranging from emotional support animals and the #MeToo movement to college safe spaces and dead celebrity holograms.